2011
DOI: 10.1111/j.1556-4029.2011.01761.x
|View full text |Cite
|
Sign up to set email alerts
|

Firing Distance Estimates with Pellet Dispersion from Shotgun with Various Chokes: An Experimental, Comparative Study

Abstract: There are several studies suggesting models for firing distance estimation due to pellet dispersion, but few of them consider the degree of choke of a shotgun. The purpose of this research is to suggest some models for estimation of the firing distance for choked and cylinder bore shotguns. Twelve gauge with full chokes, and 12 and 16 gauge with cylinder bore shotguns were fired with #2 and #5 shots from 75, 100, 300, 500, and 1000 cm distances. Statistically significant pellet dispersion values were found for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It is also important to note that we shot turkeys an additional time in the breast during harvest, which is uncommon among normal turkey-hunting practices. However, while hunters typically only shoot turkeys in the head/neck area (Keck and Langston 1992), due to the spread of a shotgun pattern (Arslan et al 2011), multiple pellets often unintentionally impact the breast muscle tissue. Further, most other species of game birds are harvested while flying and are much smaller than wild turkeys, making it common for multiple pellets to impact the breast muscle (Burger et al 1998;Johansen et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that we shot turkeys an additional time in the breast during harvest, which is uncommon among normal turkey-hunting practices. However, while hunters typically only shoot turkeys in the head/neck area (Keck and Langston 1992), due to the spread of a shotgun pattern (Arslan et al 2011), multiple pellets often unintentionally impact the breast muscle tissue. Further, most other species of game birds are harvested while flying and are much smaller than wild turkeys, making it common for multiple pellets to impact the breast muscle (Burger et al 1998;Johansen et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Arslan et al showed that the distribution of pellets on a target surface depends on factors such as the type and caliber of the weapon, the length and diameter of the barrel, the degree of choke, the type of the gunpowder and the loading of the shotshell, as well as the environmental conditions that were present at the time of the shot [7]. Maitre et al demonstrated the importance of the distance between the barrel of the firearm and the victim, as well as the degree of the barrel's narrowing (choke) in shaping the distribution of pellets, in relation to the length of the barrel weapon that seems to affect the dispersion of pellets to a lesser extent [8].…”
Section: Current Methodsmentioning
confidence: 99%